2008
DOI: 10.1038/nrmicro1952
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of microbial traversal of the blood–brain barrier

Abstract: Central nervous system (CNS) infections continue to be an important cause of morbidity and mortality. Microbial invasion and traversal of the blood–brain barrier is a prerequisite for CNS infections. Pathogens can cross the blood–brain barrier transcellularly, paracellularly and/or in infected phagocytes (the so-called Trojan-horse mechanism). Consequently, pathogens can cause blood–brain barrier dysfunction, including increased permeability, pleocytosis and encephalopathy. A more complete understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
476
0
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(498 citation statements)
references
References 120 publications
6
476
0
16
Order By: Relevance
“…The molecular mechanisms underlying BBB invasion and the involvement of these VFs is discussed in detail elsewhere (12,50,51).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The molecular mechanisms underlying BBB invasion and the involvement of these VFs is discussed in detail elsewhere (12,50,51).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Electron microscopic (EM) studies have shown the presences of meningeal pathogens in membrane bound vacuoles within BMEC, suggesting the involvement of endocytic pathways as well as avoidance of lysosomal fusion for BBB traversal (Nizet et al 1997;van Sorge et al 2008van Sorge et al , 2011. Many studies have focused on the identification of bacterial and host components involved in microbial interactions with the BBB (Kim 2008). Critical bacterial components have been discovered by screening random mutant libraries (Badger et al 2000;Doran et al 2005), analyzing bacterial transcription profiles during infection (Dietrich et al 2003;Teng et al 2005), and using bioinformatic approaches for whole genome comparisons (Uchiyama et al 2009;van Sorge et al 2009;Tazi et al 2010).…”
Section: Microbial Adhesion To Bmec and Transcytosis Across The Bbbmentioning
confidence: 99%
“…Microbial interactions with the BBB may involve crossing of BMEC in a vacuole (transcytosis), through the intercellular junctional spaces ( paracytosis), or while inside a host cell (e.g., infected phagocyte) using it as a vehicle to cross the barrier (Trojan horse) (Kim 2008(Kim , 2010 (Fig. 2).…”
Section: Pathogen Invasion Of the Bbbmentioning
confidence: 99%
“…Under normal physiological conditions, the BBB tightly regulates transport of molecules into and out of the CNS. The restrictive nature of the BBB is a consequence of the formation of complex cell-to-cell tight junctions and lower basal levels of pinocytosis and endocytosis (3,4). Although astrocytes were once thought to serve a structural role in the BBB, it is now clear that they play an important role in maintaining its functional integrity.…”
mentioning
confidence: 99%